1994
DOI: 10.1007/bf00197386
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of hyaluronate (HA) in primary tumors and nude mouse xenografts of human pancreatic carcinomas using a biotinylated HA-binding protein

Abstract: A biotinylated hyaluronate (HA)-binding protein isolated from bovine cartilage was used to analyze the distribution of HA in nude mouse xenografts derived from human pancreatic adenocarcinoma cell lines as well as in primary human pancreatic adenocarcinomas. The most reproducible results for the localisation of HA were obtained using cryostat sections. When the biotinylated HA-binding protein was applied to histological sections of nude mouse xenografts, the specific staining found could be inhibited by preinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Various studies showed a correlation between RHAMM expression and tumour progression, lymph node metastasis or reduced overall survival time in tumours or cell lines of high metastatic potential such as invasive breast cancer (Wang et al 1998), stomach cancer (Li et al 2000), malignant melanoma, and pancreatic cancer cells. This finding is in agreement with the observation that in primary pancreatic tumours the highest HA concentrations were found at the tissue interface between the tumour mass and the normal tissue (Fries et al 1994). We showed here that 87% (13/15) of non-cancerous endometrium tissue was negative for RHAMM.…”
Section: Discussionsupporting
confidence: 93%
“…Various studies showed a correlation between RHAMM expression and tumour progression, lymph node metastasis or reduced overall survival time in tumours or cell lines of high metastatic potential such as invasive breast cancer (Wang et al 1998), stomach cancer (Li et al 2000), malignant melanoma, and pancreatic cancer cells. This finding is in agreement with the observation that in primary pancreatic tumours the highest HA concentrations were found at the tissue interface between the tumour mass and the normal tissue (Fries et al 1994). We showed here that 87% (13/15) of non-cancerous endometrium tissue was negative for RHAMM.…”
Section: Discussionsupporting
confidence: 93%
“…20 HA is a known secretory product of several human pancreatic carcinoma cell lines 21 and has been shown as an over-represented glycosaminoglycan in human PDA, 22 localised to the stroma and peritumoral connective tissue. 23 However, in contrast to other epithelial cancers, the pathological significance of its rheological and signalling properties has not been fully investigated in this malignancy. 24 In this study, we sought to investigate the aetiology of vascular compression in the KPC GEMM and identified HA as a critical modifier of tumorous vascular function.…”
Section: Significance Of This Studymentioning
confidence: 99%
“…malignant mesothelioma (Roboz er al, 1985). several types of human lung cancer (Horai et al, 1981) and human pancreatic carcinoma (Fries et al, 1994). have demonstrated a high concentration of HA in tumor tissues.…”
Section: Introductionmentioning
confidence: 99%